Do you see what I hear? Vantage point preference and visual dominance in a time-space synaesthete - Jarick, Michelle; Stewart, Mark T.; Smilek, Daniel; Dixon, Michael J. (Frontiers in Psychology, 2013)
Time-space synaesthetes ‘see’ time units organized in a spatial form. While the structure might be invariant for most synaesthetes, the perspective by which some view their calendar is somewhat flexible. One well-studied synaesthete L adopts different viewpoints for months seen versus heard. Interestingly, L claims to prefer her auditory perspective, even though the month names are represented visually upside down. To verify this, we used a spatial-cueing task that included audiovisual month cues. These cues were either congruent with L’s preferred ‘auditory’ viewpoint (auditory-only and auditory + month inverted) or incongruent (upright visual-only and auditory + month upright). Our prediction was that L would show enhanced cueing effects (larger response time difference between valid and invalid targets) following the audiovisual congruent cues since both elicit the 'preferred' auditory perspective. Also, when faced with conflicting cues, we predicted L would choose the preferred auditory perspective over the visual perspective. As we expected, L did show enhanced cueing effects following the audiovisual congruent cues that corresponded with her preferred auditory perspective, but that the visual perspective dominated when L was faced with both viewpoints simultaneously. The results are discussed with relation to the reification hypothesis of sequence space synaesthesia (Eagleman, 2009).